Hesperetin upregulates Fas/FasL expression and potentiates the antitumor effect of 5-fluorouracil in rat model of hepatocellular carcinoma. Issue 1 (1st January 2020) - Aboismaiel, Merna G.; El-Mesery, Mohamed; El-Karef, Amro; El-Shishtawy, Mamdouh M.
ABSTRACT: This study aimed to investigate the antitumor efficacy of hesperetin (HST) either alone or combined with 5-fluorouracil (5-FU) in thioacetamide (TAA)-induced hepatocellular carcinoma (HCC) in rats. Moreover, possible HST molecular mechanism(s) of action were investigated. Sixty male Sprague-Dawley rats were randomized into six groups ( n = 10/group); normal control (no treatment), HCC (TAA), HCC/carboxymethyl cellulose (CMC) (TAA+CMC), HST (TAA+HST in CMC), 5-FU (TAA+5-FU), HST/5-FU (TAA+HST+5-FU). Serum levels of liver enzymes (ALT and AST), bilirubin, albumin, total protein and alpha-Fetoprotein (AFP) along with hepatic contents of hepatic glutathione and mal0ndialdhyde were measured. Gene expression of Fas, FasL, caspase-8, caspase-3 and Bcl-2 were measured using real-time polymerase chain reaction. Histopathological examination was used to assess nodule size, fibrosis ratio and necroinflammatory score. HST showed improvements in hepatic functions, decreased levels of AFP and oxidative stress and restricted HCC progression. HST activated apoptosis through inducing Fas and FasL and inhibiting Bcl-2 gene expressions. Furthermore, HST/5-FU combination surpassed the results obtained from either HST or 5-FU groups. In conclusion, HST exerted its antitumor effect through induction of Fas/FasL apoptotic pathway and reduction of oxidative stress. HST and 5-FU combination provided prominent synergistic effects, thus it can be regarded as promising combination therapy for HCC.